REFLECTIONS ON DOMESTIC SPACE: THE CASE OF ENCLOSURE 353 OF LA HUERTA SITE (QUEBRADA OF HUMAHUACA, PROVINCE OF JUJUY, ARGENTINA) - Runcio, María Andrea (2011)
The paper presents some thoughts about domestic space and the dichotomy between public space and domestic space; they are based on the analysis of the evidence recovered at enclosure 353 which is located in the Inca sector of La Huerta site (Quebrada de Humahuaca, Jujuy province, Argentina).